대장암 절제술 후 정맥 혈전색전증 발생에 대한 저분자량 헤파린의 예방 효과 연구 - 이승덕(Seung Duk Lee); 박지원(Ji Won Park); 박성찬(Sung Chan Park); 김학진(Hak Jin Kim); 최효성(Hyo Seong Choi); 오재환(Jae Hwan Oh) (Annals of surgical treatment and research, 2010)
Purpose: In western society, prophylaxis for venous thromboembolism (VTE) is the standard treatment under colorectal surgery for colorectal cancer. However, the incidence of VTE after colorectal surgery and the effect of prophylactic methods are not well known in Korea. The aim of this study is to evaluate the incidence of VTE and assess the efficacy and safety of low molecular weight heparin (enoxaparin) after major colorectal surgery in Korean patients with compression stockings. Methods: From Jan. 2006 to Dec. 2008, 1,727 consecutive patients underwent major colorectal surgery. Thirty-six were excluded due to the therapeutic use of enoxaparin. A final number of 1,691 patients were included. Graduated compression stockings were used in all patients and 654 were perioperatively given enoxaparin. Only compression stocking group (group A) and compression stocking with enoxaparin group (group B) were compared in terms of VTE. The event of VTE within 6 months after surgery was counted by clinical symptoms, then imaging findings were used for confirmation. Results: Total VTE developed in 10 patients (0.6%). Three with deep vein thrombosis had pulmonary embolism. Two had only pulmonary embolism. The rates of VTE were not different between group A and B (0.8% vs. 0.3%, P=0.333). Also, postoperative major bleeding was not significantly different. However, postoperative transfusion was higher in group B (P＜0.001). Conclusion: The incidence of VTE was very low after colorectal surgery in Korean patients with compression stockings. The additional use of enoxaparin for colorectal cancer patients with compression stockings seems to have little benefit for VTE prophylaxis. KCI Citation Count: 0